Arrested Histories : Tibet, the CIA, and Memories of a Forgotten War - McGranahan, Carole (Book collections on Project MUSE., 2010)
Ethnography that looks at the production of history and memory among the exile Tibetan community, focusing on narratives of the armed resistance against the Chinese from the 1950s to the early 1970s.